Pengembangan Website Pembelajaran Materi Aset Tetap Berwujud Dengan Memanfaatkan Google Sites - Alma Rosita; Han Tantri Hardini (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2022)
Distance learning activities are considered less effective due to the limited ability to manage and utilize existing technology. Learning tends to use Power Point Slides which makes it difficult for students to understand the material of tangible fixed assets so that learning media for tangible fixed assets is needed that is effective and easy to understand. This study aims to produce a tangible fixed asset learning website and determine the feasibility of a tangible fixed asset material learning website and determine student responses to a tangible fixed asset material learning website. The test subjects were students of Accounting Education 2018 State University of Surabaya. The development model in this research is 4D (Define, Design, Development, Disseminate). Data collection techniques are using assessment questionnaires and questionnaires. The data analysis technique used descriptive analysis technique. The results of the research are in the form of a learning website with a development model carried out to the Development stage. The feasibility of the material learning website for fixed assets in the form of material aspects is in the very feasible category, the media aspect is in the very feasible category and the results of the student response questionnaire are in the very good category. So it can be concluded that the tangible fixed asset learning website is very suitable for use in secondary financial accounting learning 1.